Outside the Equality Act: Non-standard protection from discrimination in British law. (December 2015) - Hand, James
The 'single' Equality Act 2010 was intended to unify and simplify British discrimination law which had grown-up piecemeal over 40 years. However, a number of protections did not follow the standard model (as originally laid down in the Sex Discrimination Act 1975) and remained outside the unification process. Such grounds include trade union membership and the possession of whistle-blower status and past criminal records. This difference has been significant in the government's reaction to the European Court of Human Rights' decision in Redfearn v. UK regarding membership of political parties, where the government opted to expand these 'other' protections rather than amend the Equality Act 2010. This article considers the role and status of these other discriminations which remain outside the Equality Act 2010 in light of the government's response to Redfearn .